Opportunities and challenges of bi-specific antibodies - Segues, Aina; Huang, Shuyu; Sijts, Alice; Berraondo, Pedro; Zaiss, Dietmar M. (Elsevier Inc., 2022)
The recent clinical approval of different Bi-specific antibodies (BsAbs) has revealed the great therapeutic potential of this novel class of biologicals. For example, the bispecific T-cell engager (BiTE), Blinatumomab, demonstrated the unique capacity of BsAbs to link T-cells with tumor cells, inducing targeted tumor cell removal. Additionally, Amivantamab, recognizing the EGFR and cMet in cis, revealed a substantial improvement of therapeutic efficacy by concomitantly targeting two tumor antigens. Cis-targeting BsAbs furthermore allow discerning cell populations which concurrently express two antigens, for which each antigen expression pattern in itself might not be selective. In this way, BsAbs harbor the great prospect of being more specific and showing fewer side effects than monoclonal antibodies. Nevertheless, BsAbs have also faced major obstacles, for instance, in ensuring reliable assembly and clinical-grade purification. In this review, we summarize the different available antibody platforms currently used for the generation of IgG-like and non-IgG-like BsAbs and explain which approaches have been used to assemble those BsAbs which are currently approved for clinical application. By focusing on the example of regulatory T-cells (Tregs) and the different, ongoing approaches to develop BsAbs specifically targeting Tregs within the tumor microenvironment, our review highlights the huge potential as well as the pitfalls BsAb face in order to emerge as one of the most effective therapeutic biologicals targeting desired cell populations in a highly selective way. Such BsAb may improve treatment efficacy and reduce side effects, thereby opening novel treatment opportunities for a range of different diseases, such as cancer or autoimmune diseases.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Antibody platforms; Bispecific antibodies (bsAb); Bispecific T-cell engager (BiTE); IgG-like antibodies; Monoclonal antibody; Non-IgG-like antibodies; Regulatory T-cells (Tregs)